Nelson Werneck Sodré: história e utopia nos tempos do ISEB um estudo da narrativa como instrumento na disputa política 1955-1964 - Morais, Rodrigo de Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research sought to understand the participation of Nelson Werneck Sodré in political debates in Brazil about national development, between the decades of 1950-60. To this end, we analyzed the works which the author published during the years he was a member of the Instituto Superior de Estudos Brasileiros (ISEB) (1955-1964). In the analysis of works produced by the author in this period, we tried to observe the intertwined relationship established between the historical narratives produced and the author's political expectations, since he made his narrative the place par excellence of the political disputes that crashed. It was, therefore, to recover the works of Sodré from the perspective of his political engagement and choices about policies and projects of national development. His work in this regard was to develop a narrative of the past to justify the diagnosis of the problems identified in the present, in order to defend their expectations about the future - the union of Brazilian social classes to achieve the Brazilian Revolution

A presente pesquisa pretendeu compreender a participação de Nelson Werneck Sodré nos debates políticos no Brasil acerca do desenvolvimento nacional, entre as décadas de 1950-60. Para tanto, analisou as obras que o escritor publicou durante os anos em que foi membro do Instituto Superior de Estudos Brasileiros (ISEB) (1955-1964). Na análise das obras produzidas pelo autor no referido período, buscou-se observar a imbricada relação estabelecida entre as narrativas históricas produzidas e as expectativas políticas do autor, uma vez que ele fez de sua narrativa o lugar por excelência das disputas políticas que travou. Tratou-se, portanto, de recuperar as obras de Sodré a partir da perspectiva de seu engajamento político e das opções políticas e projetos acerca do desenvolvimento nacional. Seu trabalho, nesse sentido, foi o de elaborar uma narrativa de passado que justificasse o diagnóstico dos problemas que identificou no presente, com vistas a defender sua expectativa quanto ao futuro - a união das classes sociais brasileiras para a concretização da Revolução Brasileira
Keywords: Sodré, Nélson Werneck - 1911-1999; Instituto Superior de Estudos Brasileiros; História; Narrativa (Retorica); Revoluções - Aspectos políticos; História política; Brasil - Historia - Revolução - 1964